Análise comparativa de propriedades mecânicas e de durabilidade de argamassas de revestimento mistas e aditivadas - Alessandra Tolentino Souza (2019)
The purpose of this study was to analyze the influence of a set of additives in mortar coating, using mixed lime mortar as reference. To achieve this objective an adequate proportion of mortar was dosed, using natural sand, CP II-F 32 cement and CH I hydraulic lime, via SANTOS (2014) methodology. Afterwards, based on the hydraulic lime proportion the additive mortar proportion was dosed, adding different proportions of additives: water retainer (R), air entraining agent (I) and plasticizer (P), as established by SIMPLEX methodology. With the appropriate proportions some tests were conducted: consistency, density in the fresh and hardened state, water retention, modulus of elasticity, tensile strength in flexion, compression, adherence, water absorption by immersion and by capillarity, porosity, adapted aging test, and analysis of the microstructure through a digital microscope. At the end of this study, it was evidenced that: entrained air and total porosity were directly influenced by the increase of the air entraining agent; the density in fresh and hardned state and open porosity were inversely influenced by the air entraining, and directly by the plasticizer; using only air entraining or plasticizer presented an unsatisfactory adherences result, the highest result were with 50%P + 50%R, being this result as high as the one of mixed mortar; the mechanical resistance were directly influenced by the use of plasticizer; and the cost of materials were directly influenced by water retainer, however it was cheaper than mixed mortars cost of materials. In the end, it was verified the possibility (technical and economical) of replacing the mixed mortar with the additive mortar (50%P + 50%R) as efficiente as the mixed mortar studied.